Improved resistive switching phenomena observed in SiNx‐based resistive switching memory through oxygen doping process. Issue 3 (23rd December 2013) - Park, Ju Hyun; Kim, Hee‐Dong; Hong, Seok Man; Yun, Min Ju; Jeon, Dong Su; Kim, Tae Geun
Abstract The improvement of resistive switching (RS) phenomena of silicon‐nitride (SiNx)‐based resistive random access memory (ReRAM) cells through oxygen doping process was investigated. As a result, compared to un‐doped SiNx films, the oxygen doped SiNx (SiNx:O2)‐based ReRAM cells show a lower current (∼0.3 μA) level at a high resistance state and a smaller variation of operating voltage through the reduction of leakage current in the SiNx:O2 film by combining silicon dangling bonds and doped oxygen ions. Therefore, we believe that the oxygen doping process in SiNx films can effectively improve the RS characteristics of SiNx‐based ReRAM cells. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)